Network Traffic Model Based on Superposition of Single User Requests Flows - Viet Nguyen Duc; A. S. Tamazian (Известия высших учебных заведений России: Радиоэлектроника)
User session extraction from network traffic data is considered. Statistical analysis of inter-session times of infocommunication network link was performed. Q-exponential distribution was proposed to describe the inter-session times distribution. Aggregated traffic model of infocommunication network link based on superposition of short-term traffic fragments data was suggested. The aggregated traffic model was verified by means of empirical traffic data.